Studi Mini Linguistik Arab Terapan: Menganalisis Kosakata Bahasa Arab Sehari-hari - Sugito, Sugito; Tatang, Tatang; Khoirunnisa, Siti; Islamia, Fadlia Nurul; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Arabic holds a significant position in Indonesian education due to its close association with Islamic teachings and classical Islamic literature. However, Arabic language instruction in higher education remains dominated by grammatical and translation approaches, with limited emphasis on communicative aspects. This study aims to analyze the use of Arabic vocabulary in students’ daily lives and to understand its contextual application in social and academic interactions. Employing a qualitative descriptive approach, the research involved five students from the Arabic Language Education program who actively use Arabic within the campus environment. Data were collected through observation and interviews, and subsequently analyzed through processes of reduction, categorization, and contextual description. The findings reveal that students frequently employ five core vocabulary items: Assalamu’alaikum/Marhaban (greetings), Alhamdulillah (expression of gratitude), Afwan (apology), Syukran (thank you), and Al-Ma’ (water). The use of these expressions illustrates the practical application of applied Arabic linguistics in everyday communication while simultaneously reflecting religious, social, and cultural values internalized through language. Accordingly, context-based Arabic language learning is essential to enhance students’ communicative competence in an effective and meaningful manner.